Altered Intestinal Permeability and Fungal Translocation in Ugandan Children With Human Immunodeficiency Virus - Dirajlal-Fargo, Sahera (Clin Infect Dis, 2020)
BACKGROUND: Children with perinatally acquired human immunodeficiency virus (HIV; PHIVs) face a lifelong cumulative exposure to HIV and antiretroviral therapy (ART). The relationship between gut integrity, microbial translocation, and inflammation in PHIV is poorly understood. METHODS: This is a cross-sectional study in 57 PHIVs, 59 HIV-exposed but uninfected children, and 56 HIV-unexposed and -uninfected children aged 2–10 years old in Uganda. PHIVs were on stable ART with HIV-1 RNA <400 copies/mL. We measured markers of systemic inflammation, monocyte activation, and gut integrity. Kruskal-Wallis tests were used to compare markers by group and the Spearman correlation was used to assess correlations between biomarkers. RESULTS: The mean age of all participants was 7 years and 55% were girls. Among PHIVs, the mean CD4 % was 34%, 93% had a viral load ≤20 copies/mL, and 79% were on a nonnucleoside reverse transcriptase inhibitor regimen. Soluble cluster of differentiation 14 (sCD14), beta-D-glucan (BDG), and zonulin were higher in the PHIV group (P ≤ .01). Intestinal fatty acid binding protein (I-FABP) and lipopolysaccharide binding protein (LBP) did not differ between groups (P > .05). Among PHIVs who were breastfed, levels of sCD163 and interleukin 6 (IL6) were higher than levels in PHIV who were not breastfed (P < .05). Additionally, in PHIVs with a history of breastfeeding, sCD14, BDG, LBP, zonulin, and I-FABP correlated with several markers of systemic inflammation, including high-sensitivity C-reactive protein, IL6, d-dimer, and systemic tumor necrosis factor receptors I and II (P ≤ .05). CONCLUSIONS: Despite viral suppression, PHIVs have evidence of altered gut permeability and fungal translocation. Intestinal damage and the resultant bacterial and fungal translocations in PHIVs may play a role in the persistent inflammation that leads to many end-organ diseases in adults. Despite viral suppression, children with perinatally acquired human immunodeficiency virus (HIV) in Uganda have evidence of alterations in intestinal permeability and fungal translocation, compared to HIV-exposed but uninfected and HIV-unexposed children, which may play a role in HIV-associated chronic inflammation.